Retargeting of rat parvovirus H-1PV to cancer cells through genetic engineering of the viral capsid - Allaume, Xavier; Kaufmann, Johanna K.; Nettelbeck, Dirk M.; Marchini, Antonio (Journal of virology, 2012)
The rat parvovirus H-1PV is a promising anticancer agent given its oncosuppressive properties and the absence of known side effects in humans. H-1PV replicates preferentially in transformed cells, but the virus can enter both normal and cancer cells. Uptake by normal cells sequesters a significant portion of the administered viral dose away from the tumor target. Hence, targeting H-1PV entry specifically to tumor cells is important to increase the efficacy of parvovirus-based treatments. In this study, we first found that sialic acid plays a key role in H-1PV entry. We then genetically engineered the H-1PV capsid to improve its affinity for human tumor cells. By analogy with the resolved crystal structure of the closely related parvovirus minute virus of mice, we developed an in silico three-dimensional (3D) model of the H-1PV wild-type capsid. Based on this model, we identified putative amino acids involved in cell membrane recognition and virus entry at the level of the 2-fold axis of symmetry of the capsid, within the so-called dimple region. In situ mutagenesis of these residues significantly reduced the binding and entry of H-1PV into permissive cells. We then engineered an entry-deficient viral capsid and inserted a cyclic RGD-4C peptide at the level of its 3-fold axis spike. This peptide binds α(v)β(3) and α(v)β(5) integrins, which are overexpressed in cancer cells and growing blood vessels. The insertion of the peptide rescued viral infectivity toward cells overexpressing α(v)β(5) integrins, resulting in the efficient killing of these cells by the reengineered virus. This work demonstrates that H-1PV can be genetically retargeted through the modification of its capsid, showing great promise for a more efficient use of this virus in cancer therapy.